Extensive superficial dermatomycosis caused by Cladophialophora sp., a deep mycosis pathogen: A case report - Limantara, Nikko Vanda; Siswati, Agnes Sri; Yogianti, Flandiana (UI Scholars Hub, 2025)
Background: Superficial dermatomycosis, predominantly caused by dermatophytes, affects approximately 20–25% of the global population. However, non-dermatophytic fungi, such as Cladophialophora species (sp.), can also cause similar cutaneous infections. Although less common, these organisms are particularly concerning in immunocompromised individuals. Case Illustration: A 66-year-old immunocompromised male presented with widespread pruritic and erythematous patches, initially misdiagnosed as tinea corporis. Despite receiving standard antifungal therapy, his condition persisted. Further investigation through fungal culture identified Cladophialophora sp., which was resistant to common antifungal agents such as fluconazole, itraconazole, and ketoconazole. However, the fungus was sensitive to terbinafine, which has been successfully used to treat extensive superficial dermatomycosis. Discussion: This case highlights the ability of non-dermatophytic fungi, especially Cladophialophora sp., to cause extensive superficial dermatomycosis, especially in immunocompromised patients. The patient’s compromised immune system likely contributed to the extensive nature of the lesions. In this case, antifungal resistance may have been exacerbated by prior unsupervised self-medication and environmental exposure. Conclusion: We report an immunocompromised patient with inadequate prior antifungal treatment who developed extensive superficial dermatomycosis caused by Cladophialophora sp., a deep mycosis pathogen resistant to multiple azoles, highlighting the role of host immunity and inappropriate unsupervised therapy in disease severity and antifungal resistance.